Atomic spectrometry update. Review of advances in the analysis of metals, chemicals and functional materials. Issue 11 (16th September 2015) - Carter, Simon; Fisher, Andy; Garcia, Raquel; Gibson, Bridget; Lancaster, Steve; Marshall, John; Whiteside, Ian
Abstract : This review covers advances in the analysis of advanced materials, metals, fuels and lubricants, nano structures, ceramics, refractories, organic and inorganic chemicals, catalysts and nuclear materials by a range of techniques including X-ray, ICP, LIBS, mass spectrometry, synchrotron-based techniques, plus non-destructive and ablation surface techniques. Abstract : There has been significant progress in the use of laser induced breakdown spectrometry (LIBS) as a method of monitoring steel production in real time. This has the benefits of both time and cost saving. There has been a drop in the number of papers reporting methods for the analysis of fuels. This may be a function of the drop in oil prices leading to reduced finance for research. However, the determination of S is one of the hot topics in this sample type. This is possibly a consequence of companies attempting to meet the increasingly strict regulations on S emissions. Analytical methodology, e.g. LA-ICP-MS, LIBS or XRF, which produces minimal damage to the samples is still increasingly popular. This is especially true for historical or archaeological sample types, e.g. paintings, pottery and old documents; but is also applicable to forensic materials. Often, with these sample types, the analytical data are then treated using chemometrics packages so that provenance may be determined or patterns detected. Similar methodology was used for the identification of different plastics types, facilitating sorting and re-cycling. The analysis of nanoparticles is an increasingly popular subject area. Simple introduction of samples containing nanoparticles through a standard nebuliser/spray chamber sample introduction system is often complicated by the particles agglomerating. This leads to under-estimations of the concentrations present. Single particle analysis has continued to be a popular research area with real samples now being extracted and analysed rather than standard solutions. Similarly, field flow fractionation coupled with ICP spectrometry (sometimes also in conjunction with single particle analysis) has also been used to characterize nano-particulates and to distinguish between particulate and ionic species.